Crowdsourcing as Content Collaboration for STEM Edutainment - Azwin Arif, Abdul Rahim; Nor Yazi, Khamis; Mohd Shafeirul Zaman, Abd Majid; Arulselvi, Uthayakumaran; Nursyaheedah, Muhammad Isa (Horizon Research Publishing Corporation, 2021)
In this project, crowdsourcing science, technology, engineering and mathematics (STEM) content was used to promote enjoyable, challenge-based English language gamification to young ESL learners and instructors altogether. The aim is to optimize the participants’ engagement in learning STEM disciplines using the target language. However, relevant literature in this area shows inadequate empirical evidence on engagement when these two activities combined are implemented in real-life settings. This research therefore, was conducted to explore the participants’ engagement in learning STEM contents, outside their classroom setting, using crowdsourcing and gamification activities. Through needs analysis of 48 participants (school children aged 13 to 14 years) who were assisted by 20 university undergraduates who were involved in the ‘Young Scientist Camp’ project, it was discovered that the participants had minimal exposure to the use of technology as well as the language in earning STEM disciplines. The participants were assigned to crowd-source for online STEM contents because the target is to maximize the use of English language. The contents were used to form several questions which they then took turns to test their peers from other groups using Kahoot! The qualitative data of the study were gathered via video recorded interaction, observations, and focus group interviews. Tesch’s thematic analysis, Kappa coefficient for inter-rater reliability and an observation checklist using Kapp’s motivational characteristics of game elements were used to determine crowdsourcing characteristics and elements of engagement from the activities. Interestingly, the pupils showed evidence of engagement when faced by unexpected problems in their groups. They also expressed strong engagement when the autonomy was given to them in deciding the contents and flow of the activities, which was evidence in the process of completing the tasks. This implicates emerging recommendations in engaging young learners via crowdsourcing techniques and gamification to foster interest in learning the language for STEM.